2004
DOI: 10.1590/s0001-37652004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory aspects of common variable immunodeficiency

Abstract: Common variable immunodeficiency (CVID) is an immunological disorder characterized by defective antibody production, recurrent infections, most notably of the respiratory tract, autoimmune phenomena and cancer. Some CVID patients may also present disturbances of the cellular immune response such as a decrease in the number and proportion of different lymphocyte populations, diminished lymphoproliferative response to mitogens and antigens, altered production of cytokines, and deficient expression of cell-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
35

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 103 publications
0
27
0
35
Order By: Relevance
“…The primary phenotypic defect is a failure in B cell differentiation, resulting in impaired secretion of IgA, IgG and IgM (2). Diagnosis is difficult because of the infrequent incidence, high clinical variability of CVID and lack of specific laboratory tests, and is generally established years after the onset of the disease (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The primary phenotypic defect is a failure in B cell differentiation, resulting in impaired secretion of IgA, IgG and IgM (2). Diagnosis is difficult because of the infrequent incidence, high clinical variability of CVID and lack of specific laboratory tests, and is generally established years after the onset of the disease (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…CVID is characterized by markedly reduced serum levels of IgG, IgA, and often IgM (1). In addition to having low levels of Igs, patients with CVID fail to produce specific antibodies after vaccination or exposure to antigens (2). CVID patients suffer from recurrent sinopulmonary, ear, and gastrointestinal infections and have increased risk of autoimmune and lymphoproliferative diseases (1).…”
Section: Introductionmentioning
confidence: 99%
“…; other studies showed that the most frequently identifi ed organisms causing infectious diarrhea were Giardia lamblia, Campylobacter sp., and Salmonella sp. 6,7,25 Although Crypotosporidium parvum is a common pathogen among HIGM patients, 19 it was found in only one patient in our study, which could be due to the small number of these patients in the current series.…”
Section: Discussionmentioning
confidence: 58%